Reverse Commerce (Re-Commerce) Design for the Sale of Secondhand Eco print Products as an Implementation of Circular Economy in Indonesia - Rilis Akista Tria Sasti; Didiet Widiatmoko Soewardikoen; Wirania Swasty (Publikasi Indonesia, 2025)
The fashion industry contributes greatly to environmental pollution due to high production waste. One solution to reduce this impact is through the concept of a circular economy by encouraging sustainable consumption behavior, including re-commerce or reselling used goods. This study aims to design a re-commerce platform for used ecoprint products as an implementation of a circular economy in Indonesia. The methods used are the Double Diamond and Empathy Map approaches to understand user needs and design a wireframe-based UI/UX prototype. The results of the study indicate that there is great potential in the development of ecoprint re-commerce in Indonesia, supported by consumer awareness of environmentally friendly products. The designed platform,